Inhibition of ejaculation by the non‐peptide oxytocin receptor antagonist GSK557296: a multi‐level site of action. (12th July 2013) - Clément, Pierre; Bernabé, Jacques; Compagnie, Sandrine; Alexandre, Laurent; McCallum, Stewart; Giuliano, François
Abstract : Background and Purpose: Oxytocin (OT) plays a major role in the control of male sexual responses. Notably, blockade of OT receptors has been reported to inhibit ejaculation in animals. The study aimed to investigate the action of a highly selective, non‐peptide OT antagonist GSK557296 in a model of pharmacologically induced ejaculation in anaesthetized rats. The site of action was assessed by investigating different delivery routes for this compound. Experimental Approach: Urethane‐anaesthetized Wistar rats were implanted with a cerebral ventricle cannula for i.c.v. injections or with a subdural catheter for intrathecal (i.t.) GSK557296 injections. Occurrence of ejaculation was assessed following i.v. 7‐hydroxy‐2‐(di‐N‐propylamino)tetralin (7‐OH‐DPAT), a dopamine D3 receptor agonist. In addition, seminal vesicle pressures (SVP) and bulbospongiosus muscle (BS) EMG were recorded as physiological markers of emission and expulsion phases of ejaculation respectively. Key Results: Highest i.v. GSK557296 dose reduced occurrence of ejaculation and increases in SVP but had no effect on BS‐EMG. I.c.v. GSK557296 dose dependently inhibited ejaculation, increases in SVP and BS contractions. At spinal thoracic level, GSK557296 dose dependently inhibited ejaculation and increases in SVP but BS‐EMG was impaired only with the highest dose. When delivered at lumbar level, GSK557296 dose dependently inhibited ejaculation, increases in SVP and BS contractions. Conclusions and Implications: In the 7‐OH‐DPAT‐induced ejaculation model, GSK557296 acts peripherally and centrally to inhibit ejaculation with different modalities. Blockade of brain OT receptors seems to be the most effective mechanism of action. Targeting central OT receptors with highly selective antagonist seems a promising approach for the treatment of premature ejaculation.